The Influence of the Jigsaw Learning Model on student learning outcomes and engagement at Madrasah Tsanawiyah Al-Ikhlas Aek Botik - Gultom, Dinda Sri Fatimah; Dewi, Salamiah Sari; Surbakti, Amanah (Jurnal Psikologi Terapan dan Pendidikan, 2025)
This research is motivated by the low learning outcomes and limited student engagement at MTs Al-Ikhlas Aek Botik. The purpose of this study is to determine the effect of the jigsaw learning model on students' learning outcomes and engagement. The research employed a quasi-experimental design with a Pretest-Posttest Control Group format. The study involved 42 seventh-grade students divided into two groups: an experimental group that received instruction using the jigsaw learning model, and a control group that received conventional instruction. The instrument used to measure learning outcomes and student engagement was a multiple-choice questionnaire. The data were analyzed using normality and homogeneity tests, followed by the Paired Sample t-test, the Independent Sample t-test, the Wilcoxon test, and the Mann-Whitney test. The results indicated a significant difference between pre-test and post-test scores in the experimental group. Additionally, student engagement in the experimental group increased significantly compared to the control group. Therefore, the research concluded that the jigsaw learning model has a significant positive effect on learning outcomes and student engagement at MTs Al-Ikhlas Aek Botik.